Imaging diagnosis of intracranial atherosclerosis stenosis-related large vessel occlusion before and during endovascular therapy - Yoshimoto, Takeshi (Frontiers in Neurology, 2023)
It is becoming increasingly important to identify the type of stroke, especially the mechanism of occlusion, before and during its treatment. In the case of intracranial atherosclerotic stenosis-related large vessel occlusion, it is necessary to develop a treatment strategy that includes not only mechanical thrombectomy but also adjunctive therapies such as primary or rescue therapy (percutaneous angioplasty, intracranial/carotid stenting, local fibrinolysis) and perioperative antithrombotic therapy. However, in clinical practice we often encounter cases where it is difficult to identify the occlusive mechanism before endovascular treatment because of insufficient information in the minimal circumstances of the hyperacute phase of stroke. Here we focus on the imaging diagnosis before and during treatment of intracranial atherosclerotic stenosis-related large vessel occlusion with in situ thrombotic occlusion as the mechanism of thrombotic occlusion, based on previous reports. We describe the diagnosis of intracranial atherosclerotic stenosis-related large vessel occlusion from the perspectives of “thrombus imaging,” “perfusion,” and “occlusion margin.”